2017
DOI: 10.1371/journal.pone.0182230
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction after holmium laser enucleation of the prostate (HoLEP): A prospective cohort study

Abstract: ObjectiveTo investigate patient satisfaction after holmium laser enucleation of the prostate (HoLEP) in a prospective study.Subjects and methodsFrom May 2012 to December 2014, 397 patients underwent HoLEP by a single surgeon and enrolled in our prospective registry. Baseline data included age, PSA, transrectal ultrasonography, the international prostate symptom score (IPSS), and overactive bladder symptom score (OABSS). Subjective assessment of surgical outcomes was performed at 6 months postoperatively using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
3
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 33 publications
5
25
3
2
Order By: Relevance
“…As expected, SUI had a substantial negative impact on quality of life. This result is in line with previous reports showing the quality of life impact that incontinence can have on patients (26).…”
Section: Discussionsupporting
confidence: 93%
“…As expected, SUI had a substantial negative impact on quality of life. This result is in line with previous reports showing the quality of life impact that incontinence can have on patients (26).…”
Section: Discussionsupporting
confidence: 93%
“…Lee et al . showed that a higher IPSS voiding score and higher QOL score were found after HoLEP . Woo et al .…”
Section: Factors Influencing Improvement Of Uroflowmetry After Holep mentioning
confidence: 97%
“…5 Lee et al showed that a higher IPSS voiding score and higher QOL score were found after HoLEP. 6 Woo et al stated the weight of the resected prostate contributed to improving postoperative Q max and post-void residual urine volume. 7 Mu et al reported that the operation for BPH >70 mL improved the functional outcome.…”
mentioning
confidence: 99%
“…First, a newly developed exercise method can be provided to reinforce hip extensor muscle in patients with incontinence after radical prostatectomy. Furthermore, a new exercise method can be adopted to treat stress urinary incontinence in women and incontinence in men after transurethral prostatectomy such as holmium laser enucleation of the prostate [ 25 ].…”
Section: Discussionmentioning
confidence: 99%